Analisis Pengaruh Demografi dan Geografi pada Technology Acceptance Model: Studi pada Penggunan Shoee Paylater Masyarakat Solo Raya - Salma Nur Aini; Sarjiyanto Sarjiyanto (Jurnal Sosioteknologi, 2023)
The demographic and geographical conditions of the community are thought to have an influence on technology acceptance. However, there are not many studies which have evaluated the demographic and geographical conditions of the community in terms of the use of technology, especially application-based technology that directly interacts with the community. This study uses a modified technology acceptance model (TAM) as a theoretical framework. This case study investigates whether community demographics and geography influence the acceptance of Shopee Paylater among the people of Solo Raya. The model was validated using a questionnaire obtained from an online survey in the former Surakarta Residency as a representative for the people of Solo Raya. The results show that demographic conditions such as gender, age, and income and geographical conditions of residence have no significant influence on the technology acceptance model (TAM), which means demographic and geographical differences have no impact on the acceptance of technology within Solo society, especially the Shopee Paylater application. It is because there are no differences in access to technology or income levels in the Solo Raya. This research also shows that in a society that is relatively modern and has access to adequate infrastructure, it tends to be adaptive to new technology.